Identification of key transporters mediating uptake of aconitum alkaloids into the liver and kidneys and the potential mechanism of detoxification by active ingredients of liquorice. Issue 28 (23rd May 2019) - He, Yufei; Wang, Ze; Wu, Weidang; Xie, Ying; Wei, Zihong; Yi, Xiulin; Zeng, Yong; Li, Yazhuo; Liu, Changxiao
Abstract : Liquorice may alleviate the toxicity of bioactive ingredients of aconite by inhibiting transporters mediating uptake in the liver/kidneys. Abstract : Aconite as a commonly used herb has been extensively applied in the treatment of rheumatoid arthritis, as pain relief, as well as for its cardiotonic actions. Aconitum alkaloids have been shown to be the most potent ingredients in aconite, in terms of efficacy against disease, but they are also highly toxic. Apart from neurological and cardiovascular toxicity exposed, the damage to hepatocytes and nephrocytes with long-term use of aconitum alkaloids should also be carefully considered. This study attempted to investigate the critical role of uptake transporters mediating the transport of aconitum alkaloids into the liver and the kidneys. The resulting data revealed that hOATP1B1, 1B3, hOCT1 and hOAT3 were mainly involved in the uptake of aconitum alkaloids. Additionally, the inhibitory effects of bioactive ingredients of liquorice on uptake transporters were screened and further confirmed by determining the IC50 values. The in vitro study suggested that liquorice might lower the toxicity of aconite by reducing its exposure in the liver and/or kidneys through inhibition of uptake transporters. Eventually, the in vivo study was indicative of detoxification of liquorice by decreasing the exposure of aconitine as representative compound in liver after co-administration, even though the exposure in kidney altered was less significant. In summary, hOATP1B1, 1B3, hOCT1 and hOCT3 were determined as the key uptake transporters mediating the transport process of aconitum alkaloids into the liver and/or kidneys, and liquorice may alleviate the toxicity caused by reduction of exposure through inhibition of those key uptake transporters.